Avaliação da eletrocoagulação com eletrodo telado de alumínio para o tratamento de efluente oleoso sintético - Thomes, Marcelly da Conceição (2023)
The generation of oily effluents represents an imminent challenge, influenced by population growth, industrial expansion, and increased global production. This problem results in the contamination of soil, water, and atmosphere, with adverse consequences for ecosystems, biodiversity, and human health. Electrocoagulation (EC) emerges as a promising solution, using electrochemical processes to precipitate solid metallic contaminants. This study is based on developing a new type of aluminum electrode, which is economically viable and easy to handle, aiming to improve effectiveness in the treatment of oily effluents. Experiments with synthetic oily effluent in a batch EC reactor (total volume: 4.5 liters) explored voltage variations (10, 15 and 20 volts) and polarity inversion times (10, 20, and 30 seconds). Parameters such as oil and grease content (TOG), turbidity, pH, temperature, mass loss of the electrodes used, electrical energy consumption, and aluminum content in the effluent after treatment were analyzed. Percentage removal in oil and grease content of up to 98±1% was obtained with screened electrodes. The percentage reduction in turbidity was also greater than 98% in most tests, as well as the pH, temperature, and aluminum content after treating the oily effluent, were within the parameters for effluent discharge. The results obtained in this study suggest that aluminum mesh screen electrodes can be an efficient and sustainable alternative for companies and industries that need to treat oily effluents.